Innovation by Mergers and Acquisitions: Paradox of Acquired Organization’s Leadership Teams Commitment to Internal Innovation - Hassan, Samia Mohamood (2013)
Acquisitive growth has become an integral part of global organizations strategy in recent years, leading to more focus on M&A outcomes, how these merged organizations realize synergies to respond to favourable market conditions and the effect it has on their human capital. Especially, the influence the merger process has on the managers of the merging organizations with the significant increased size, diversification, behavioural procedural controls and increased use of leverage, all leading to the absorption of the managers time. This dissertation highlights the trade off between growth via M&A and executive leadership team commitment to internal innovation (R&D). It is based on the results gathered from the employees of organizations XYZ and ABC which has combined to form a resultant entity DRC, part of a conglomerate called AIMI. This paper will be limited to determining the effects of mergers and acquisition on innovation. It will seek to determine how managers’ commitment to innovations is affected by the drive to pursue acquisitions and mergers. It is worth noting that acquisition and mergers are not a negative development. However, the dissertation will seek to analyze the negative side and specifically on the effects of mergers and acquisitions on innovation. How the success of targeted M&A’s leads to the creation of a risk-averse culture and a self fulfilling cycle in which M&A serves as a substitute to innovation.